Measuring negative emotional responses to climate change among young people in survey research: a systematic review protocol. Issue 10 (3rd October 2022) - Martin, Gina; Cosma, Alina; Roswell, Tasha; Anderson, Martin; Leslie, Kathleen; Card, Kiffer G; Closson, Kalysha; Kennedy, Angel M; Gislason, Maya K
Abstract : Introduction: Many young people report experiencing negative emotional responses to their awareness of climate change and the threats it poses to their future. With that, an increasing number of survey instruments have been developed to examine young people's negative emotional responses to their awareness of climate change. This report describes a protocol for a systematic review that aims to identify, synthesise and critically appraise how negative emotional responses to climate change among young people have been measured in survey research. The research questions addressed in this review are: (1) How has negative emotional responses to climate change been defined and measured among young people? (2) How do survey instruments measuring young people's negative emotional responses to climate change vary in terms of reliability and validity? (3) What factors are associated with negative emotional responses to climate change among young people? Methods and analysis: Seven academic databases (CINAHL, ERIC, MEDLINE, PsycINFO, Web of Science, Scopus, and Environment Complete) will be searched to retrieve studies published between 1 January 2006 and 31 March 2022 and published in English. Studies including survey instruments that measure negative emotional responses among young people (aged 10–24 years) will be eligible for inclusion. Targeted journals will be hand-searched. This review will follow Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines for systematic reviews. The methodological quality, in terms of reliability and validity, of the included studies will be assessed using the Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN) checklist for risk of bias of patient-reported outcome measures. To rate the quality of the instruments, we will use a modified Grading of Recommendations, Assessment, Development and Evaluations technique defined by the COSMIN guidelines. Ethics and dissemination: Ethical approval is not applicable for this study. We will disseminate the findings through publication in peer-reviewed journals and presentations. PROSPERO registration number: CRD42022295733.